2017
DOI: 10.21608/ejdr.2017.7137
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Seed Soaking and Foliar Spraying With Selenium on the Growth and Yield of Lettuce Under Saline Stress

Abstract: he implementation of proper agricultural practices is important for reducing the effect of salt stress in plants. Therefore, this experiment was conducted in 2014/2015 and 2015/2016 seasons at Ras Sudr station of Desert Research Center, South Sinai Governorate, Egypt, to determine the most effective selenium (Se) dose and application method on lettuce plants Bruma cultivar under salt stress conditions. Six different Se treatments; Se0 (without application as a control), Se1 (seed soaking in 30 µmol l -1 for 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Generally, selenium nanoparticle application by foliar spraying resulted in higher contents of dry matter, N and K in the coriander plants under saline stress which has a positive impact on the permeability and activity the cellular membrane, redistribution of some essential elements and it regulated uptake. These results are consistent with the work of (Hawrylak-Nowak, 2008;Feng et al, 2013;Abul-Soud and Abd-Elrahman 2016;Castillo-Godina et al, 2016 andShalaby et al, 2017).…”
Section: Fig 10 Interaction Between Salinity Levels and Seleniumsupporting
confidence: 93%
“…Generally, selenium nanoparticle application by foliar spraying resulted in higher contents of dry matter, N and K in the coriander plants under saline stress which has a positive impact on the permeability and activity the cellular membrane, redistribution of some essential elements and it regulated uptake. These results are consistent with the work of (Hawrylak-Nowak, 2008;Feng et al, 2013;Abul-Soud and Abd-Elrahman 2016;Castillo-Godina et al, 2016 andShalaby et al, 2017).…”
Section: Fig 10 Interaction Between Salinity Levels and Seleniumsupporting
confidence: 93%
“…Examples of the photosynthesis parameters measurements are net photosynthesis rate, stomatal conductance, rubisco activity, carbohydrate content, and chlorophyll content. 7,105,113,114 The impact of CQD on plant development have been evaluated and compared to that of control plants, with the majority of the research focusing on photosynthetic enhancement. Stomatal conductance (g l ) is a measurement of the amount of stomatal opening in plants and is used to determine the amount of water in the plant.…”
Section: Effects Of Cqd On Plant Growth and Photosynthesis Ratementioning
confidence: 99%
“…It also induces metal (cadmium) stress tolerance in radish plants (Miao et al 2008). Later on, lettuce seeds were investigated, and results shown that selenium-soaked lettuce seeds are tolerant towards salinity and gives good growth and yield (Shalaby and Ramadan 2017). However, selenium content in biofortified plants through seed soaking is lower than other methods.…”
Section: Seed Soakingmentioning
confidence: 99%